Reduced glenohumeral rotation, external rotation weakness and scapular dyskinesis are risk factors for shoulder injuries among elite male handball players: a prospective cohort study - Clarsen, B.; Bahr, R.; Haugsboe Andersson, S.; Munk, R.; Myklebust, G. (British Journal of Sports Medicine, 2014)
Aim To determine whether rotator cuff strength, glenohumeral joint range of motion and scapular control are associated with shoulder injuries among elite male handball players. Methods A total of 206 players in the Norwegian elite handball league for men were tested prior to the 2011-2012 season. Measures included: (1) glenohumeral internal and external rotation range of motion, (2) isometric internal rotation, external rotation and abduction strength and (3) assessment of scapular dyskinesis. Players were followed prospectively for the entire regular season (30 weeks), with shoulder problems registered bi-weekly using the Oslo Sports Trauma Research Center Overuse Injury Questionnaire. A cumulative severity score was calculated for each player based on their questionnaire responses. This was used as the outcome measure in risk factor analyses. Results The average prevalence of shoulder problems throughout the season was 28% (95% CI 25% to 31%). The prevalence of substantial shoulder problems, defined as those leading to moderate or severe reductions in handball participation or performance, or to time loss, was 12% (95% CI 11% to 13%). Significant associations were found between obvious scapular dyskinesis (OR 8.41, 95% CI 1.47 to 48.1, p<0.05), total rotational motion (OR 0.77 per 5° change, 95% CI 0.56 to 0.995, p<0.05) and external rotation strength (OR 0.71 per 10 Nm change, 95% CI 0.44 to 0.99, p<0.05) and shoulder injury.